Study of denture-induced fibrous hyperplasia cases diagnosed from 1979 to 2001 - Firoozmand, Leily Macedo; Almeida, Janete Dias [UNESP]; Guimarães Cabral, Luiz Antonio [UNESP] (My University, 2005)
Objective: The purpose of this research was to study the cases of inflammatory fibrous hyperplasia (IFH) at the Clinic of Semiology, Department of Bioscience and Oral Diagnosis, São José dos Campos Dental School, State University of São Paulo, Brazil. Methods and materials: A total of 141 clinical file cards indicating a final diagnosis of IFH, from the archives of the Department of Bioscience and Oral Diagnosis and dated from 1979 to 2001, were included in the study. Of these files, 50 indicated a diagnosis of denture-induced fibrous hyperplasia. Sex, age, race, duration, and clinical features that confirm their classification in the non-neoplastic proliferating process were analyzed statistically. Results: Of the 50 analyzed cases of denture-induced lesion, 22% occurred in men and 78% in women. Patients in the age group of 41 to 50 years presented the highest frequency of the lesion. Conclusions: Inflammatory fibrous hyperplasia occurs more frequently in women (71.63%), and denture-induced lesions appear mainly in patients over 40 years of age (70% of cases). Patients with denture-induced hyperplasia reported pain associated with the lesion (70%).
Keywords: Denture; Diagnosis; Hyperplasia; Inflammation; Medical examination; Medical history